Tapering of femtosecond laser-written waveguides - Heilmann, Rene; Greganti, Chiara; Graefe, Markus; Nolte, Stefan; Walther, Philip; Szameit, Alexander (Applied Optics, 2018)
The vast development of integrated quantum photonic technology enables the implementation of compact and stable interferometric networks. In particular, laser-written waveguide structures allow for complex 3D circuits and polarization-encoded qubit manipulation. However, the main limitation in the scaling up of integrated quantum devices is the single-photon loss due to mode–profile mismatch when coupling to standard fibers or other optical platforms. Here we demonstrate tapered waveguide structures realized by an adapted femtosecond laser writing technique. We show that coupling to standard single-mode fibers can be enhanced up to 77% while keeping the fabrication effort negligible. This improvement provides an important step for processing multiphoton states on chip.
CRIS-Team Scopus Importer:2023-04-20